Pengaruh TPAK, Pendidikan, dan Inflasi terhadap Pertumbuhan Ekonomi di Provinsi Termiskin Se-Indonesia - Todi, Dhiya' Salsabila; Anggraeni, Erike; Susanto, Is (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the influence of TPAK, education, and inflation on economic growth in the poorest provinces in Indonesia using a sample of 10 provinces during the period 2015 to 2023 and is analyzed from an Islamic economic perspective. The purpose of this study is to examine how economic factors that affect the rate of economic growth based on Islamic values can be applied to achieve fairer and more equitable economic growth in the 10 poorest provinces in Indonesia. The research method used is quantitative, with a panel data regression analysis approach to test hypotheses about the relationship between the variables mentioned. The data was obtained from official sources such as Indonesia's Central Statistics Agency (BPS), covering the level of labor force participation, education level, regional inflation, and GDP. The results of the analysis show that the level of labor force participation and education level have a negative effect on the rate of economic growth in the 10 poorest provinces in Indonesia. Meanwhile, the inflation rate has a positive influence on the rate of economic growth in the 10 poorest provinces in Indonesia. Simultaneously, labor force participation rates, education levels, and regional inflation together have a positive effect on the rate of economic growth in the 10 poorest provinces in Indonesia. This study highlights to consider the factors that have been analyzed as a design to increase the rate of economic growth in Indonesia. With a deeper understanding of these factors, it is hoped that it can provide a better picture for the future economic growth rate.